Efeitos da suplementação de fosfatidilserina isolada ou associada à maltodextrina e/ou aminoácidos de cadeia ramificada sobre desempenho aeróbio e anaeróbio e biomarcadores de estresse fisiológico - Guimarães Neta, Júlia Costa (2018)
The aim of this study was to obtain more knowlegde about the effects of phosphatidylserine (PS) in physical exercise. For this, two works were carried out, the first one was a bibliographical survey about PS and its impact on physical performance. The findings demonstrated a potential ergogenic effect for athletes of runing, cycling and intermittent exercise, however some studies relate PS supplementation in anaerobic exercise. More specific studies on the mechanism of action responsible for this ergogenic action are needed for a better understanding of the physiological role of PS. The second one investigated the effect of PS supplementation isolated or associated with maltodextrin and/or branched chain amino acids on anaerobic and aerobic performance, hormonal and metabolic responses in Wistar rats. The participants were separated in four groups according to the administered supplement: PS, PS + BCAA, PS + BCAA + CHO and placebo (PLA). All groups performed na exercise protocol that consisted of alternating high intensity (HIIT) and moderate intensity (MIT) swimming sessions. Two-way ANOVA was used to identify as a differential between groups over time without aerobic and anaerobic performance. To compare concentration values of CK, muscle and hepatic glycogen, testosterone, corticosterone, catalase (CAT), volume and training load, one-way ANOVA followed by Tukey's post hoc was used. There was no difference in anaerobic performance (p=0,76) and aerobic capacity (p=0,172) between groups after experimental tests. However, total training volume ,in the first and second week, and total training load, in first week, was lower in PLA group compared to others supplemented (p<0,05). The CK concentration was higher in the PS group compared to the PS + BCAA group (p=0,04) and PS + BCAA + CHO (p=0,01). In the liver, glycogen concentration was lower in the PS + BCAA compared to the PS group (p=0,008) and PS + BCAA + CHO (p=0,02). PS + BCAA + CHO presented a 180% greater glycogen concentration in the soleus compared to PLA (p=0,03) and 170% greater compared to PS (p=0,03). Testosterone/corticosterone ratio was higher in PS + BCAA group compared to others groups (p<0,05). No significant changes were observed in the concentration of lactate, testosterone, corticosterone and CAT enzyme activity.